Pengaruh Soft Skill, Praktik Pengalaman Lapangan (Magang) Dan Motivasi Kerja Terhadap Kesiapan Kerja Mahasiswa Di Bank Syariah - Nurjannah, Nurjannah; Walian , Armansyah; Lemiyana, Lemiyana (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to determine the influence of soft skills, practical field experience or internships and work motivation on student work readiness at Sharia Bank. The data collection technique was carried out using a questionnaire data collection method using a Likert scale. The population in this study was 501 sharia banking students at UIN Raden Fatah Palembang, class of 2020-2021. Sample collection in this study was carried out using a non-probability sampling technique, using a purposive sampling method. The sample in this study consisted of 125 students. Data analysis uses descriptive analysis and multiple linear regression analysis with the help of the IBM SPSS version 26 analysis program. Based on the research results, it can be concluded that: (1) soft skills have a positive and significant effect on students' work readiness in sharia banks, (2) Field experience practice (internships) have a positive and significant effect on students' work readiness in sharia banks, (3) Work motivation has an effect positive and significant impact on students' work readiness in sharia banks and (4) simultaneously soft skills, practical field experience (internships) and work motivation have a joint effect on students' work readiness in sharia banks.